El ideal de juez local Tenancingo, Intendencia de México, 1795-1800 - Claudia Guarisco (Caravelle)
This text examines the problem of the legitimacy of the Spanish Monarchy in a rural parish in central New Spain, at the end of 18th century. Local judges (subdelegados) who violated the local justice culture lost their legitimacy. This culture, distant from official practices, was used by Officers of the Royal Court to convey the people’s expectations in conflict with their immediate authorities in terms of official justice. Forgiveness between the parties set an end to the crisis. It was in that coming and going from custom to law and doctrine and back to local values that the engagement between Crown and subjects laid.